Polysaccharide as a Separation Medium for Gel Electrophoresis - Tsutomu Arakawa; Masataka Nakagawa; Chiaki Sakuma; Yui Tomioka; Yasunori Kurosawa; Teruo Akuta (Polysaccharides, 2024)
Gel electrophoresis and size exclusion chromatography (SEC) are vital techniques in biochemical research, employing gel matrix structures made of polysaccharides or synthetic polymers like polyacrylamide for the analysis and separation of macromolecules. Polysaccharides, such as agarose, offer safer alternatives to acrylamide. Polysaccharide gels, notably agarose, facilitate the analysis and purification of proteins and nucleic acids through a molecular sieving mechanism. Gel electrophoresis for proteins is mainly divided into denaturing and native methods. Denaturing electrophoresis with sodium dodecyl sulfate (SDS) simplifies protein migration but disrupts molecular interactions. Conversely, native gel electrophoresis, without SDS, allows proteins to migrate based on the running pH and the isoelectric point of the proteins, while nucleic acids consistently migrate toward the anode. The electrophoresis of proteins with variable charges presents complexes. This review focuses on the use of polysaccharides, particularly agarose, for native gel electrophoresis, highlighting their applications in separating macromolecules. It also discusses the applications and limitations of agarose gels when used as a matrix for electrophoresis. Such information should help in designing electrophoresis experiments using polysaccharides.